A estrutura da comunidade de macro-invertebrados bentônicos em três represas do médio rio Tietê (SP), com ênfase nas espécies exóticas Melanoides tuberculata (Gastropoda, Thiaridae) e Corbicula fluminea (Bivalvia, Corbiculidae) - Suriani, Ana Lucia (2006)
The reservoirs are artificial ecosystems constructed by the man and attend to the multiple uses. The reservoir provokes alterations in the aquatic ecosystem, causing modifications in the chemical and physical composition of the sediment and of the water and consequently in the circulation and the organization of the biological communities. The purpose of this study was to characterize the taxonomic composition and the benthic community density in 3 reservoirs of the Middle Tietê River (Barra Bonita, Bariri and Ibitinga), to analyze the physical and chemical characteristics of the water and of the sediment and to verify the possible relation of these with the structure of the benthic community, considering the populations of the native species and the invading species Melanoides tuberculata and Corbicula fluminea. The samplings were carried out in two climatic periods, the rainy season (November 2002) and the dry season (August 2003), showing three portions in each reservoir (upper, middle and lower) and following a sweeping with 6 sampling points in each transect. In each point, the samples of sediment were collected in duplicate with one drag of the type van Veen. Based on the limnological data the reservoirs of Barra Bonita and Bariri were classified as whereas Ibitinga Reservoir was characterized as mesotrophic for the periods evaluated. In November 2002, 21, 29 and 25 taxa of macroinvertebrates were registered in Barra Bonita, Bariri and Ibitinga reservoirs, respectively, while in August 2003, there were 23, 31 and 27 taxa, respectively, in each reservoir. A greater similarity between the benthic macroinvertebrates was found for the associations sampled in both periods in the same reservoir than between the different reservoirs, evidencing that each environment have a particular composition of taxa, although some taxa are common among them. The invading species M. tuberculata e C. fluminea were current in all the reservoirs, in both periods of sampling, except in the Barra Bonita reservoir. The generalized occupation of M. tuberculata and the high densities of this specie in the studied reservoirs reveal the high invading potential of same and the probable competition with the native species.